Hadith #1327 - Sahih al-Bukhari - Abi Aiyub (Sahih al-Bukhari)
Once the Prophet (ﷺ) went out after sunset and heard a dreadful voice, and said, “The Jews are being punished in their graves.”
Grade: Sahih

Hadith #1350 - Sahih al-Bukhari - Abi Aiyub (Sahih al-Bukhari)
A man said to the Prophet (ﷺ) “Tell me of such a deed as will make me enter Paradise.” The people said, “What is the matter with him? What is the matter with him?” The Prophet (ﷺ) said, “He has something to ask. (What he needs greatly) The Prophet (ﷺ) said: (In order to enter Paradise) you should worship Allah and do not ascribe any partners to Him, offer prayer perfectly, pay the Zakat and keep good relations with your Kith and kin.” (See Hadith No. 12, Vol 8).
Grade: Sahih